How I diagnose and treat patients in the pre-fibrotic phase of primary myelofibrosis (pre-PMF): practical approaches of a German expert panel discussion in 2024 - Griesshammer, Martin; Al-Ali, Haifa Kathrin; Eckardt, Jan-Niklas; Fiegl, Michael Andreas; Göthert, Joachim Rudolf; Jentsch-Ullrich, Kathleen; Koschmieder, Steffen; Kvasnicka, Hans Michael; Reiter, Andreas; Schmidt, Burkhard; Heidel, Florian (Annals of hematology, 2025)
The prefibrotic phase of primary myelofibrosis (pre-PMF) represents a distinct subentity within the spectrum of myeloproliferative neoplasms (MPNs), recognized by the World Health Organization (WHO) and the International Consensus Classification (ICC). Pre-PMF is characterized by unique morphological, clinical, and molecular features, distinguishing it from essential thrombocythemia (ET) and overt myelofibrosis (overt-PMF). The diagnostic process for pre-PMF relies on bone marrow histology, identification of molecular mutations and exclusion of other myeloid neoplasms. Misclassification remains a significant challenge due to overlapping phenotypes and the heterogeneity of clinical presentations, which range from asymptomatic cases to severe cytopenias and a high thrombotic risk. Management strategies for pre-PMF focus on mitigating symptom burden, reducing thromboembolic events, and preventing disease progression. Low-risk patients often benefit from observational approaches or low-dose aspirin, while cytoreductive therapies, such as hydroxyurea or interferon-alpha, are utilized in symptomatic or high-risk cases. JAK inhibitors like ruxolitinib have shown promise in addressing splenomegaly and systemic symptoms, although their role in pre-PMF requires further investigation. Advances in artificial intelligence are enhancing diagnostic precision by refining bone marrow histopathological analysis, paving the way for more accurate disease classification and tailored therapeutic strategies. This position paper integrates insights from a German expert panel discussion, underscoring the need for interdisciplinary collaboration, adherence to updated WHO/ICC diagnostic criteria, and personalized treatment approaches. By addressing diagnostic challenges and therapeutic nuances, it seeks to improve outcomes and quality of life for patients navigating the complexities of pre-PMF.
Online veröffentlicht: 31. Januar 2025
Gesehen am 28.07.2025